Analisis Perkembangan Akademik Siswa Tunagrahita dalam Lingkungan Pendidikan Inklusif pada Kelas V di SDN Kebun Bunga 1 - Ridhaningtyas, Latifa Putri (Lembaga Yasin AlSys, 2025)
This study aims to analyze the academic development of students with learning disabilities in an inclusive education environment in grade V at SDN Kebun Bunga 1, focusing on learning strategies, teacher support and their impact on students' academic outcomes. The main issues faced were challenges in inclusive learning, including limited resources and the implementation of effective strategies. With a qualitative approach using the PRISMA method, data was collected through observation, interviews and document analysis. The results show that material simplification, individualized guidance, and the use of interactive learning media play a significant role in improving the understanding and independence of students with disabilities. Despite facing cognitive and emotional limitations, students showed progress in reading skills, concept understanding, and social interaction. The implications of this study are the need for more in-depth teacher training, close collaboration with parents, and the development of more innovative learning media to support inclusive education. This research contributes to the development of adaptive and inclusive education strategies for students with special needs.